Elaeocarpus tectorius derived phosphorus-doped carbon as an electrode material for an asymmetric supercapacitor. (5th December 2019) - Nirosha, Bose; Selvakumar, Rajendran; Jeyanthi, Jeyadharmarajan; Vairam, Sundararajan
Abstract : Phosphorus-doped activated carbon from unexplored biomass was prepared, and it exhibits excellent electrochemical properties for green energy technology. Abstract : Phosphorus-doped porous carbon is prepared from a new biomass ( Elaeocarpus tectorius ) at three different temperatures using a facile H3 PO4 activation approach. The physicochemical characterisation of the as-prepared carbons by X-ray diffraction, Raman spectroscopy, thermal analysis, scanning electron microscopy, N2 adsorption–desorption isotherms and X-ray photoelectron spectroscopy indicates that the carbon obtained at 900 °C possesses a high phosphorus content, 2.5% (by mass), and a large interlayer distance of the porous carbon with more expanded channels facilitating the penetration of ions into the interlayers and a rapid adsorption of ions suitable for ultra-high volumetric capacitance. The optimized carbon (900 °C) delivers high gravimetric capacitance (385 F g −1 at 0.2 A g −1 ) and volumetric capacitance (543 F cm −3 at 0.2 A g −1 ) in 1 M H2 SO4 . In 1 M Na2 SO4 electrolyte, it still exhibits a gravimetric capacitance of 203 F g −1 at 0.3 A g −1 and a volumetric capacitance of 286 F cm −3 at 0.3 A g −1 . Additionally, a coin cell asymmetric device fabricated using this carbon works in a wide potential window from 0 to 1.5 V with 96% capacitance retention in 1 M H2 SO4 aqueous electrolyte for 1000 cycles and yields a high energy density of 27 W h kg −1, showing the utility for the development of wearable electronic devices.